2021
DOI: 10.3389/fphys.2021.661171
|View full text |Cite
|
Sign up to set email alerts
|

Cinaciguat Prevents Postnatal Closure of Ductus Arteriosus by Vasodilation and Anti-remodeling in Neonatal Rats

Abstract: Closure of the ductus arteriosus (DA) involves vasoconstriction and vascular remodeling. Cinaciguat, a soluble guanylyl cyclase (sGC) activator, was reported with vasodilatory and anti-remodeling effects on pulmonary hypertensive vessels. However, its effects on DA are not understood. Therefore, we investigated whether cinaciguat regulated DA patency and examined its underlying mechanisms. In vivo, we found that cinaciguat (10 mg/kg, i.p. at birth) prevented DA closure at 2 h after birth with luminal patency a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…We placed a Swan-Ganz in the pulmonary artery of neonatal lambs on postnatal day 3 and gave a lower daily dose of (35 μg/kg x day, i.v. for 7 days: 245 μg/kg total) from postnatal day 4–10 Cinaciguat than that used by Hung et al, 2021 in newborn rats. Cinaciguat treatment induced an acute decrease in pulmonary arterial pressure for 45 min, which then leveled off until the next dose of Cinaciguat the following day.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…We placed a Swan-Ganz in the pulmonary artery of neonatal lambs on postnatal day 3 and gave a lower daily dose of (35 μg/kg x day, i.v. for 7 days: 245 μg/kg total) from postnatal day 4–10 Cinaciguat than that used by Hung et al, 2021 in newborn rats. Cinaciguat treatment induced an acute decrease in pulmonary arterial pressure for 45 min, which then leveled off until the next dose of Cinaciguat the following day.…”
Section: Discussionmentioning
confidence: 97%
“…Control newborns infused with vehicle did not display changes in any of the variables studied (data not shown). Recently, Hung et al, 2021 , reported that administration in term newborn rats (10 mg/kg, i.p. at birth) prevented the closure Cinaciguat of the ductus arteriosus, which normally occurs around 2 h after birth in rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NO may cause endothelium-dependent and independent relaxations. When NO is generated from L-arginine due to NO Synthase (NOS) action, it activates guanylate cyclase (GC) and produces guanine nuclear glucoside 3',5'-cyclic phosphate (cGMP) which further leads to cGMP-dependent protein kinase (PKG)-mediated vasodilation [ 16 18 ]. In particular, the endothelium-derived NOS (eNOS) mediating eNOS-GC-cGMP-PKG pathway plays a key role in maintaining endothelium dependent vascular tone [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%